EPISTEMOLOGICAL REFLECTIONS ON MALES AND ALIENATED MASCULINITIES - Figueroa Perea, Juan Guillermo (Revista Sexología y Sociedad, 2016)
THE PURPOSE OF THIS ESSAY IS TO REFLECT ON SOME OF THE THEORETICAL, ANALYTICAL AND POLITICAL DIMENSIONS OF DIFFERENT PROCESSES OF CLASSIFICATION OF THE CATEGORIES OF BEING A MAN. IT IS ALSO A PURPOSE TO PRESENT THESE REFLECTIONS AS A PROPOSAL THAT STRUCTURES SOME RESEARCH FINDINGS, AS WELL AS THE ASSUMPTIONS THAT SUPPORT THE CONSTRUCT OF INFORMATION PRODUCTION, INCLUDING THE ASSESSMENT OF EXISTING INFORMATION FROM OTHER STUDIES THAT DO NOT SPECIFICALLY ALLUDE TO MALES AS A POPULATION. IN ORDER TO DEFINE MY THEORETICAL, POLITICAL AND EXISTENTIAL POSITION, I HAVE USED SUCH CONCEPTS AS ALIENATION AND PROPERTY OVER THE MEANS OF PRODUCTION IN WHAT IS CALLED “MASCULINITY.” FINALLY, A PROPOSAL IS OFFERED FOR THE DE-ALIENATION AND REAPPROPRIATION OF THE MEANS OF PRODUCTION BY THE RESPECTIVE ENTITIES AS HUMAN BEINGS. KEY WORDS: MALES, MASCULINITY, ALIENATION, TYPOLOGIES, BEING A MAN